SCIENTIFIC FOUNDATIONS AND MODERN APPROACHES TO PREVENTING POSTOPERATIVE INFECTIONS IN SURGICAL PRACTICE - Tuychiev Golibzhon Urmonzhonovich; Mirkomilova Sug`diyona Abdug`ani qizi (Scholar Express Journals, 2025)
Postoperative infections (POI) are among the most common and serious complications in surgical practice. This article analyzes the scientific foundations and modern approaches to preventing POI. The study is based on clinical observations and statistical analyses. Preventive measures, including strict adherence to hygiene and antiseptic protocols, rational use of antibiotic prophylaxis, thorough preoperative preparation of patients, and ensuring a sterile environment, are emphasized. Additionally, the effectiveness of advanced technologies, such as automated monitoring of risk factors and robotic surgical techniques, is evaluated. The results indicate that integrated approaches to infection prevention significantly reduce postoperative complications and enhance the efficiency of treatment processes. This article provides relevant recommendations for improving surgical practice quality, ensuring patient safety, and preventing infectious complications.
Keywords: Postoperative infections; infection prevention